Comparative study of the quality characteristics of fresh noodles with regular salt and alkali and the underlying mechanisms. (25th April 2018) - Li, Man; Sun, Qing-Jie; Han, Chuan-Wu; Chen, Hai-Hua; Tang, Wen-Ting
Highlights: Salted and alkaline noodles showed significant differences in rheology and texture. Both NaCl and alkali promoted starch gelatinization and increased cooking loss. Alkali increased starch viscosity and β -sheet protein structure compared with NaCl. Alkali induced more protein aggregates during cooking and shorter T2 time than NaCl. NaCl induced a fibrous gluten structure while alkali led to a membrane-like structure. Abstract: The quality properties of fresh noodles with NaCl and alkali were characterized by rheological, cooking, and texture properties. Microstructure, starch viscosity, protein conformation, gelatinization and protein polymerization during cooking, and water status were determined to investigate the mechanisms underlying their quality differences. The results showed that alkali induced more significantly increased ( P  < .05) gluten strength and noodle hardness, while NaCl resulted in superior dough extensibility. Pasting viscosity of alkali-flour increased and protein conformation changes were detected in alkaline noodles with increased β -sheet and decreased α -helix structures. Both NaCl and alkali increased cooking loss. NaCl induced a fibrous gluten structure while alkali caused a membrane-like structure. Furthermore, remarkable protein aggregates were observed in alkaline noodles immediately after 2 min of cooking in non-reduced HPLC patterns, while 4 min in reduced patterns. Water–solids interaction in alkaline noodles was enhanced with decreased water mobility. NaCl induced no significant changes in protein aggregation and water status.